Legal and Administrative Analysis of Discretion in Public Policy Implementation in Indonesia - Heru Wahyudi; Jaka Maulana (International Journal of Social Sciences and Humanities, 2026)
A This study analyzes administrative discretion in public policy implementation in Indonesia from legal and administrative perspectives. Discretion is an essential instrument in government administration because public officials often face legal gaps, unclear norms, urgent public needs, and complex implementation contexts that cannot always be fully regulated by written laws. However, discretion also creates legal risks when it is exercised beyond the scope of authority, contrary to the purpose of authority, in violation of procedures, or without adequate accountability. This study uses normative juridical research with a qualitative approach, applying statutory and conceptual approaches. The analysis focuses on Law Number 30 of 2014 concerning Government Administration, administrative law principles, public policy implementation, abuse of authority, accountability, and the protection of citizens’ rights. The findings show that discretion has a dual position. On the one hand, it functions as an instrument of administrative responsiveness in policy implementation. On the other hand, it may become a source of abuse of authority if it is not controlled by legality, public interest, proportionality, accountability, and the general principles of good governance. Therefore, administrative discretion must be regulated, documented, supervised, and open to legal and administrative review. This study contributes to administrative law and public policy studies by offering an integrated legal-administrative framework for understanding discretion as both a public authority and an administrative instrument in Indonesian public administration.